Derivación de Valores Económicos de la Producción de Leche de Bovinos en el Cantón Pujilí Utilizando Funciones de Beneficio. - Lozada Herrera, Lesly Karina (2022)
This research work aims to derive the economic values of milk production of bovines in the Canton Pujilí, using benefit functions, for which surveys, observation and visits to owners were carried out in order to collect data, from this it was determined that out of a total of (303) animals, there is a greater number of females (65. 7%), as for the category, it was determined that there is a high number of calves (33%), an average surface of (1.2 ha) was obtained, the average value of liters produced per day is low (6 kg), the density of milk average is not profitable (26.5) and the most predominant disease within the sector is mastitis (38%); Through the methodological development, it can be analyzed that it is necessary to implement strategies and programs of genetic improvement in the zone, so that the milk production has a cost benefit, since at the moment the producers do not have adequate profits, being their average production per month of (224.90) US dollars of which (116.46) is invested for cattle maintenance, obtaining a minimum profit. The selection criteria considered the most important are density, weight in liters per day of milk and daily weight gain. Therefore, this research fulfills the main objective of deriving the economic values of milk production of bovines in the canton of Pujili, through a quantitative methodological approach. After analyzing the results obtained from this research, it can be affirmed that the neighborhoods studied lack good cattle management, leading to inadequate milk production and low economic benefit.